Pengaruh Sumber Daya Insasi dan Strategi Penghimpunan Zakat Terhadap Minat Masyarakat Pada Kantor Layanan Zakat Rumah Yatim Ar Rahman - Dahrani Dahrani; Fadillah Rosady (CERED Indonesia Institute, 2023)
. This research uses quantitative methods with descriptive methods. This study uses primary data and secondary data as data sources. This study used questionnaires and documentation as data collection techniques. This study uses a Likert scale technique as a research instrument. Prerequisite tests in this study include validity tests, reliability tests, and normality tests. In analyzing research data, researchers used a regression test which included a simultaneous test (F), partial test (t), and test of the coefficient of determination (R2). The results of this study indicate that the two variables, namely Human Resources (X1) and Zakat Collection Strategy (X2), have a significant influence on Public Interest in the office. Human Resources (X1) has a significant influence with a tcount of 1.926 and a significance of 0.02. Meanwhile, the Zakat Collection Strategy (X2) also has a significant effect with a tcount value of 4.041 and a significance of 0.03. In addition, these two variables together also make a significant contribution to Community Interest with an fcount value of 9,693 and a significance of 0.01. The coefficient of determination (R Square) of 58.1% indicates that 58.1% of the variation in Community Interests can be explained by Human Resources and Zakat Collection Strategies.